A P5 Approach to m-Health: Design Suggestions for Advanced Mobile Health Technology - Gorini, Alessandra; Mazzocco, Ketti; Triberti, Stefano; Sebri, Valeria; Savioni, Lucrezia; Pravettoni, Gabriella (Frontiers in Psychology, 2018)
In recent years, technology has been developed as an important resource for healthcare management, especially in regard to chronic conditions. In the broad field of eHealth, mobile technology (mHealth) is increasingly used to empower patients not only in disease management but also in the achievement of positive experiences and experiential growth. mHealth tools are considered powerful because, unlike more traditional Internet-based tools, they allow patients to be continuously monitored and followed by their own mobile devices and to have continual access to resources (e.g., mobile apps or functions) supporting healthcare management activities. However, the literature has shown that, in many cases, such technology not accepted and/or adopted in the long term by its users. To address this issue, this article reviews the main factors influencing mHealth technology acceptance/adoption in healthcare. Finally, based on the main aspects emerging from the review, we propose an innovative approach to mHealth design and implementation, namely P5 mHealth. Relying on the P5 approach to medicine and healthcare, this approach provides design suggestions to address mHealth adoption issues already at the initial stages of development of the technologies.